Evalvacija na področju socialnega varstva v Sloveniji - Rihter, Liljana (Socialno delo, 2007)
At present, when so many problems erode the welfare state, evaluations are mainly used for determining the efficacy and effectiveness of programmes. The author analyses the evaluations that have been carried out in the field of social care in Slovenia. She notes that the normative basis to carry out evaluations is not binding, and that their implementation is anticipated only for programmes that are co-funded by the pertaining ministry. Nevertheless, a great number of evaluations and self-evaluations were carried out between 1997and 2001, but they were not used for decision-making of a greater importance. The conclusion is that evaluations, in order to serve their purpose, need to become more firmly rooted on both normative and operative level.
Keywords: raziskovalni načrt; uspešnost; učinkovitost; efficiency; evalvacija; socialno varstvo; Slovenia; Slovenija